A rare cause of bacteremia due to Porphyromonas asaccharolytica in a patient with necrotizing fasciitis. (October 2021) - Cobo, Fernando; Pérez-Carrasco, Virginia; Sánchez-Martin, Victoria; García-Salcedo, José A.; Martín, Elvira Barrón; Navarro-Marí, José María
Abstract: Porphyromonas species are Gram-negative anaerobic bacilli mainly involved in human periodontal diseases. We report an uncommon case of bacteremia due to P. asaccharolytica in a patient with necrotizing fasciitis. A 52-year-old woman with a history of diabetes mellitus was admitted for an extensive necrotizing lesion on the left lower limb. After she developed septic shock, two sets of blood cultures were taken. Anaerobic bottles yielded a pure culture of a microorganism initially identified as P. uenonis by MALDI-TOF MS but with a low log score, and a gene sequencing technique was therefore applied, identifying the isolate as P. asaccharolytica. Only resistance to penicillin and clindamycin was documented. Treatment with meropenem was administered, and the patient was discharged following her recovery. Highlights: Porphyromonas asaccharolytica has been rarely associated with bacteremia. The probable source of infection was a necrotizing fasciitis. MALDI-TOF MS is sometimes unable to provide definitive species differentiation. This isolate only showed resistance to penicillin and clindamycin.